Prosecutorial Misconduct: Quelling the Tide of Improper Comment to the Jury - Celebrezze, Frank D. (1987)
The United States Supreme Court, in Darden v. Wainwright, stated that where the error is forensic in nature, appellate courts should reverse a conviction when the prosecutor's misconduct so infected the trial with unfairness as to make the resulting conviction a denial of due process. Therefore, except in the most egregious cases, appellate courts are placed in the uncomfortable position of condemning the prosecutor's behavior while affirming the conviction, thus fostering what an appellate judge once called a deplorably cynical attitude towards the judiciary. This article will focus on one aspect of prosecutorial misconduct which has been chronicled with alarming regularity in recent state court decisions: improper prosecutorial remarks during argument to the jury in criminal trials. While frustrating, I do not believe the continuing problem of such misconduct is intractable. Appellate courts can deal firmly and fairly with such improper remarks and impose sanctions other than reversal where appropriate. The most effective remedy, however, lies with prompt action by the trial participants, that is, the trial court, defense counsel and the prosecutor. Ultimately, the instances of prosecutorial abuse will be reduced only when informed and educated prosecutors police themselves